Toward an Empirical Prioritization of Contingency Variables for Business Strategy - Hambrick, Donald C.; Lei, David (Academy of Management Journal, 1985)
This study, based on data from the Profit Impact of Market Strategies (PIMS) program, is a preliminary attempt to prioritize contingency variables for the field of business strategy. Chow tests for structural homogeneity shed light on the relative degrees of overall significance of ten widely-cited contingency variables. User sector, consumer or industrial, was the contingency variable that emerged as most potent among those examined. Implications for researchers and executives are suggested.